UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MELALUI PENDEKATANPEMBELAJARAN MATEMATIKA REALISTIK DI KELAS VIII SMP NEGERI 17 MEDAN T.A 2015/2016 - Khairun Nisyah Harahap; Denny . Haris (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2016)
AbstractThis study was carried out (1) to improve students mathematical problem solving ability through mathematics learning approach at the eight grade students of SMP Negeri 17 Medan T.A 2015/2016, (2) to find the improvement of students mathematical problem solving ability through mathematics learning approach at the eight grade students of SMP Negeri 17 Medan T.A 2015/2016. The participants of this study were the 32 students of VIII-2 class of SMP Negeri 17 Medan and the objective of the study was improving students mathematical problem solving ability in prism an limas subject. The method of this study was classroom action research. The instruments of this study were test and observation. This study was consisted of two cycles; each cycle consisted of two meetings. The improvement of the problem solving ability could be seen from each step of problem solving in the intial capability test, problem solving ability test I and problem solving solving ability test II. In the step of problem solving, the score in the initial capability test was 59,20 (low), problem solving ability test I was 80,08 (high), problem solving ability test II was 89,45 (high). In the step of  constructuring plan of problem solving, the score in the initial capability test was 45,80 (very low), problem solving ability test I was 72,88 (average), problem solving ability test II was 81,47 (high). In the step of doing plan of problem solving, the score in the initial capability test was 52,05 (low), problem solving ability test I was 78,61 (average), problem solving ability test II was 85,38 (high). In the step crosscheck, the score in the initial capability test was 29,69 (very low), ), problem solving ability test I was 71,48 (average), problem solving ability test II was 81,25 (high). So, it was obtained that the lowest step in the problem solving ability was the step of crosscheck. Furhermore, the ability of the researcher in managing lessons increased from cycle I to cycle II. In pre-activity 2,63 became 3,12. In main activity 2,47 became 3,05. In post-activity 2,75 became 3,75. So, it was concluded that realistic mathematics learning approach did improve the mathematical problem solving ability of the eight students of SMP Negeri 17 Medan in prism and limas subject.Kata kunci : realistic mathematics learning approach, problem solving